Cleanroom installations for SRF cavities at the Helmholtz Institute Mainz. (November 2019) - Kürzeder, T; Aulenbacher, K; Barth, W; Burandt, C; Conrad, J; Dziuba, F; Gettmann, V; Heine, R; Hug, F; Lauber, S; List, J; Miski-Oglu, M; et al.
Abstract: At the Helmholtz-Institut Mainz (HIM) a cleanroom has been equipped with new tools and installations for the planned treatment of different superconducting RF-cavities. Therefore, the cleanroom had to be shut down and some walls and part of the ceiling had to be dismantled. In its ISO-class 6 area a large ultrasonic and a conductance rinsing bath has been installed. A high pressure rinsing cabinet has been implemented between the ISO-class 6 and 4 cleanroom so that a cavity can be loaded and unloaded from both sides. For drying the ISO-class 4 cleanroom was equipped with a 160°C vacuum oven. Afterwards the cleanroom was sealed again and put back in operation. New cleanroom lift trolleys allow the handling of heavy objects (max. 200 kg). By a rail system in the cleanroom floor it is possible to move entire cold strings through the different clean room classes separated by a roll-up door. This paper reports on the reclassification of the cleanroom after it went back to operation and first experiences with its cleaning. Particle measurements of equipment in operation will be presented as well.